Improving Teachers' Knowledge Sharing Behavior with Islamic Work Ethics - Musoli; Seto Satriyo Bayu Aji (www.amertainstitute.com, 2025)
The purpose of this study is to empirically examine teachers' perceptions of their work at school. The research design uses a quantitative approach through research instruments. The unit of analysis in this study is school teachers in Yogyakarta who have worked and taught at school for at least one year. Data were collected through the direct distribution of questionnaires by the research team. Purposive sampling was used to collect samples in this study. The number of respondents in this study was 32, who were school teachers in Yogyakarta. The results of this study indicate that the hypothesis stating that Islamic work ethics have a positive but insignificant influence on knowledge-sharing behavior is rejected.